Introduction to the Special Issue: Religion in Extractive Zones - Terra Schwerin Rowe; Christiana Zenner; Lisa H. Sideris (Religions)
Religion and extractivism—like other aspects of a petroculture (Petrocultures Research Group 2016; Wilson et al [...]